(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Swimming requires optimal physical condition, particularly arm muscle strength, which plays an important role in generating propulsion in the water. This study aims to develop an arm muscle strength training device based on resistance bands using a support pole for athletes of Berang-Berang Swimming Club. The research method used is Research and Development (R&D) with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were 15 athletes divided into small group trials and large group trials. Data collection instruments included questionnaires for material expert validation, media expert validation, and athlete response questionnaires, with data analysis conducted using descriptive quantitative methods in the form of percentages. The results showed that the material expert validation in stage I obtained a percentage of 94% and stage II 98%, while the media expert validation in stage I was 88% and stage II was 94%, all of which were categorized as very good. The results of the small group trial obtained a percentage of 88% and the large group trial 91%, while the effectiveness test reached 95%, all categorized as very good. These findings indicate that the developed training media is practical, safe, and effective in improving arm muscle strength and athlete training motivation. Therefore, the resistance band-based training media with a support pole is highly feasible to be used as an alternative tool for arm muscle strength training in swimming athletes.